Psychological Stress and Job Insecurity in Tech-Enabled Workplaces - Ali , Hamza (ACADEMIA International Journal for Social Sciences, 2025)
The high rate of technology adoption in work places has altered the structure of jobs, expectations as well as their experiences. On the one hand, technological development improves performance, but on the other hand, it creates special stress factors and increases job insecurity. The workplaces that are tech enabled require continuous learning, flexibility, and digital capabilities which in most instances exacerbate the psychological strain between employees. Job insecurity which can be described as the perceived risk of losing jobs or other adverse developments in the employment terms and conditions has become one of the major issues in such environments. In this paper, the relationship between psychological stress and job insecurity within tech-enabled work environments is discussed, with the negative aspects of organizational practices, employee resilience, and technological pressures influencing employee health. Recent studies provide evidence that job insecurity, at high levels, has a detrimental effect on mental health issues, motivation, and commitment to the organization. On the other hand, stress can be minimized when supportive factors, including skill development programs, open communication, and flexible work schedules, are put in place in an organization. The results highlight the great importance of strategic human resource intervention and management strategies that would strike a balance between technological performance and psychological safety of staff. The study is relevant to the knowledge of how current technological changes affect workplace stressors and provides knowledge on how a productive and healthy workforce can be maintained.